2015
DOI: 10.1186/s13054-015-1070-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation and analysis of prognostic scoring systems for critically ill patients with cirrhosis admitted to ICU

Abstract: IntroductionThe number of patients admitted to ICU who have liver cirrhosis is rising. Current prognostic scoring tools to predict ICU mortality have performed poorly in this group. In previous research from a single centre, a novel scoring tool which modifies the Child-Turcotte Pugh score by adding Lactate concentration, the CTP + L score, is strongly associated with mortality. This study aims to validate the use of the CTP + L scoring tool for predicting ICU mortality in patients admitted to a general ICU wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Whilst MELD did perform well on this cohort, it is limited by the lack of an easily accessible grading system to stratify patient into groups and hence identify patients with a high risk of mortality. Similarly, the RFH score, which has been validated for short-term outcome in both the specialist and general settings [11, 24], failed to perform as well in this long-term study. The Child–Pugh + Lactate score attempted to meet this need with the incorporation of a measure of acute illness correlated with poor short-term outcome [5].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Whilst MELD did perform well on this cohort, it is limited by the lack of an easily accessible grading system to stratify patient into groups and hence identify patients with a high risk of mortality. Similarly, the RFH score, which has been validated for short-term outcome in both the specialist and general settings [11, 24], failed to perform as well in this long-term study. The Child–Pugh + Lactate score attempted to meet this need with the incorporation of a measure of acute illness correlated with poor short-term outcome [5].…”
Section: Discussionmentioning
confidence: 98%
“…However, ROC curve analysis alone is unlikely to provide a true measure of a score’s clinical usefulness [24, 31]. A classification system with mortality rates for each class is far easier for clinicians to interpret and apply at the bedside, which a score alone does not permit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Campbell et al. studied a retrospective cohort of 84 critically ill patients with cirrhosis and demonstrated that lactate on admission to ICU was significantly associated with ICU mortality with an aOR of 1.89 . Finally, Edmark et al.…”
Section: Discussionmentioning
confidence: 99%